1967
DOI: 10.1104/pp.42.6.881
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Sugars in Cucurbita melopepo IV. Effects of Temperature Change

Abstract: Sulmmary. A study has been made of the temperature control of translocation localized to regions of the stem, petiole and hypocotyl of Cucurbita mielopepo. The basipetal and acropetal movement of translocated 14C-labeled compounds in the phloem tissue, measured over a 45-minute period, was almost completely inhibited at 00. At 100 a partial inhibition occurred while an extremely variable degree of inhibition occurred at 150. Above 150 to 350 temperature ceased to be a limiting factor in the movement of 14C-lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…The site of synthesis of sucrose (and possibly galactinol) is thought to be the photosynthetic mesophyll tissues (14,17,18). This spatial transport in response to low temperature has been demonstrated previously in cucurbits (21,22), but the effects of low temperature were shown to be transient and quickly reversed upon removal of the chilling stress (21,22). The transience of chilling responses may also explain the transience of the carbohydrate accumulations that were seen in the present study.…”
Section: Leaf Tissue Carbohydrate Analysissupporting
confidence: 68%
See 1 more Smart Citation
“…The site of synthesis of sucrose (and possibly galactinol) is thought to be the photosynthetic mesophyll tissues (14,17,18). This spatial transport in response to low temperature has been demonstrated previously in cucurbits (21,22), but the effects of low temperature were shown to be transient and quickly reversed upon removal of the chilling stress (21,22). The transience of chilling responses may also explain the transience of the carbohydrate accumulations that were seen in the present study.…”
Section: Leaf Tissue Carbohydrate Analysissupporting
confidence: 68%
“…In cucurbits, therefore, the effects of chilling on carbon partitioning within leaf tissues may be even more complex than is currently understood for sucrose-translocating species, in light of the importance of calcium balance in the control of solute movement through plasmodesmata (14). Although the effects of chilling on phloem transport per se have been extensively investigated in cucurbit species in the past (21,22), little information exists concerning the effects of chilling on the biochemical carbon partitioning between stachyose and other metabolites within the cucurbit source leaf. The present study was, therefore, instigated to characterize the accumulation patterns and export profiles of assimilates in cucurbit source leaves following exposure of plants to chilling stress, with the aim of determining whether carbon partitioning at low temperature follows the patterns predicted by current conjectural models for stachyose-translocating plants.…”
mentioning
confidence: 99%
“…No evidence for any perturbation in photosynthetic rate coincident with petiolar cooling was obtained. Webb (13,14) has similarly observed that localized temperature treatments of the petiole did not affect the rates of "CO2 assimilation in that leaf's blade. Thus the major perturbation induced in translocation rates by cooling cannot be ascribed to a photosynthetic artifact.…”
Section: Resultsmentioning
confidence: 95%
“…Lee et al (2004) measured positive root pressure in cucumber plants. To test this possibility, we relied on the fact that root pressure rapidly declines when roots are chilled (Lee et al, 2004), whereas cold inhibition of phloem transport is a localized phenomenon (Webb, 1967). Therefore, root chilling should inhibit xylem water flux, but not sap movement through sieve tubes, in the aerial portion of the plant.…”
Section: Water From the Xylemmentioning
confidence: 99%
“…To test the source of the sap experimentally, we took advantage of the fact that long-distance phloem transport in cucurbits is severely inhibited by cold (Webb, 1967). To conduct these tests, an approximately 10-cm region near the middle of a cucumber petiole was packed in ice, kept in place with cheesecloth.…”
mentioning
confidence: 99%